Molecularly Imprinted Nanomaterials with Stimuli Responsiveness for Applications in Biomedicine - Zhang Yan; Wang Qinghe; Zhao Xiao; Ma Yue; Zhang Hongbo; Pan Guoqing (MDPI, 2025)
The review aims to summarize recent reports of stimuli-responsive nanomaterials based on molecularly imprinted polymers (MIPs) and discuss their applications in biomedicine. In the past few decades, MIPs have been proven to show widespread applications as new molecular recognition materials. The development of stimuli-responsive nanomaterials has successfully endowed MIPs with not only affinity properties comparable to those of natural antibodies but also the ability to respond to external stimuli (stimuli-responsive MIPs). In this review, we will discuss the synthesis of MIPs, the classification of stimuli-responsive MIP nanomaterials (MIP-NMs), their dynamic mechanisms, and their applications in biomedicine, including bioanalysis and diagnosis, biological imaging, drug delivery, disease intervention, and others. This review mainly focuses on studies of smart MIP-NMs with biomedical perspectives after 2015. We believe that this review will be helpful for the further exploration of stimuli-responsive MIP-NMs and contribute to expanding their practical applications especially in biomedicine in the near future.